Nutritional aspects of cognitive impairment - Djuricic, Ivana (Archives of Pharmacy, 2020)
Many scientific arguments in this area, implicate low level of important nutrients in cognitive decline, simultaneously suggesting better nutritional status as an important goal in the management of cognitive aging. Key nutrients for the protection of cognitive function are B-group vitamins, polyphenols, vitamin D, and omega-3 polyunsaturated fatty acids (PUFAs). The body of scientific evidence widely supports the roles of folic acid and metabolically related B6 and B12 vitamins in protecting cognitive function in old age. High concentrations of polyphenols in dementia therapy showed a significant increase in cerebral blood volume. Although low vitamin D blood levels were associated with a higher risk of developing dementia, vitamin D supplementation alone was not sufficient to improve cognitive outcomes. In relation to the role of omega-3 PUFAs, research findings indicate protective effects in individuals with cognitive decline. The importance of diets and a healthy lifestyle in the prevention of cognitive impairment are extensively accepted. The Mediterranean diet is the most investigated dietary pattern in observational studies. MIND diet (Mediterranean-DASH Intervention for Neurodegenerative Delay) is updated dietary approach of the Mediterranean-DASH diets. Its components are linked to dementia prevention and overall neuroprotection. It is also reported that regular physical activity maintains the brain function improving blood flow and oxygen supply.